Hypofractionation in Hepatocellular Carcinoma – The Effect of Fractionation Size. Issue 5 (May 2022) - Lewis, S.; Barry, A.; Hawkins, M.A.
Abstract: The use of stereotactic body radiotherapy (SBRT) in hepatocellular carcinoma (HCC) has increased over the years. Several prospective studies have demonstrated its safety and efficacy, and randomised trials are underway. The advancement in technology has enabled the transition from three-dimensional conformal radiotherapy to highly focused SBRT. Liver damage is the primary limiting toxicity with radiation, with the incidence of grade 3 varying from 0 to 30%. The reported radiotherapy fractionation schedule for HCC, and in practice use, ranges from one to 10 fractions, based on clinician preference and technology available, tumour location and tumour size. This review summarises the safety and efficacy of various SBRT fractionation schedules for HCC.